Snapshots of hunger in the developing world - International Food Policy Research Institute (Welthungerhilfe, 2015)
This interactive tool is designed for exploration of the data of the Global Hunger Index (GHI). It was developed using Tableau and is available at https://public.tableau.com/profile/ifpri.td7290#!/vizhome/2015GHI/Hungeraroundtheworld